Advantaged Bidders in Franchise Auctions - Vincent van den Berg (Tinbergen Institute, 2012)
Consider a government that auctions a franchise for, e.g., an airport, telecommunication network, or utility. Consider an 'incumbent bidder' that owns a complement or substitute. With an auction on the transfer (i.e. payment) to the government, the incumbent is advantaged.If the government regulates the market with an auction on the price asked to consumers, it depends who is advantaged. With complements, the incumbent is advantaged: it can set a lower price on the new franchise, as this increases the profit of the other. With substitutes, the incumbent is disadvantaged. In many settings, the advantage bidder always wins.
urn:NBN:nl:ui:31-1871/39441
Keywords: D43; L13; L51; R41; R42; 330; Franchising; auctions; advantaged bidders; incumbent; private supply; regulatory auctions; Franchising; Auktionstheorie